Self-rated benefits and knowledge gain from e-learning: the longitudinal use of an online learning experience at an international medical school - Maria G. Zavala-Cerna; Augusto E. Caballero; Steffi Verbeeck-Mendez; Michael J. Parker (BMC Medical Education)
Abstract The COVID-19 pandemic forced schools worldwide to change the delivery of the medical curriculum to an exclusively online format. Some important findings after this experience highlight the possibility of continuing with the online form of curriculum delivery, at least partially, to reinforce the learning experience of medical students. Our research goal was to analyze the benefits that medical students can gain after exposure to high-quality e-learning. Our primary aim was to analyze the gain of knowledge, as well as self-rated benefits and understanding, after exposure to high-quality e-learning. We conducted a retrospective study to report on the outcomes achieved after 3 years of experience with the online delivery of basic biomedical science courses. Measurements included knowledge gain based on pre-and post-course quizzes, self-rated evaluation of the benefit and understanding of topics on a per-lesson basis, and number and percentages of students obtaining specific certificate outcomes. We included results from 1,546 students and 2,613 course enrollments in two different medical programs. We found significant increases in self-reported benefit and understanding of topics, as well as significant increases in knowledge gain irrespective of students’ pre-course knowledge levels, as measured by the pre-course quiz. The information presented here could be used to make decisions about the incorporation of e-learning into the medical curriculum.